Influenza vaccination coverage against seasonal and pandemic influenza and their determinants in France: a cross-sectional survey - de Valk Henriette; Vaillant Véronique; Le Strat Yann; Guthmann Jean-Paul; Van Cauteren Dieter; Vaux Sophie; Lévy-Bruhl Daniel (BMC, 2011)
Abstract Background Following the emergence of the influenza A(H1N1)2009 virus, the French ministry of health decided to offer free vaccination against pandemic influenza to the entire French population. Groups of people were defined and prioritised for vaccination. Methods We took a random sample of the population of mainland France and conducted a retrospective cross-sectional telephone survey to estimate vaccination coverage against seasonal and pandemic influenza and to identify determinants of these vaccinations. Results 10,091 people were included in the survey. Overall seasonal influenza vaccination coverage (IVC) remained stable in the population from the 2008-2009 season to the 2009-2010 season reaching 20.6% and 20.8% respectively. Overall pandemic IVC in the French population is estimated to be 11.1% (CI95%: 9.8 - 12.4). The highest pandemic IVC was observed in the 0-4 years age group. For individuals with health conditions associated with higher risk of influenza, pandemic IVC was estimated to be 12.2% (CI95%: 9.8 - 15.1). The main determinants associated with pandemic influenza vaccine uptake were: living in a household with a child < 5 years ORadj: 2.0 (CI95%: 1.3 - 3.1) or with two children < 5 years or more, ORadj: 2.7 (CI95%: 1.4 - 5.1), living in a household where the head of the family is university graduate (>2 years), ORadj: 2.5 (CI95%: 1.5 - 4.1), or has a higher professional and managerial occupation, ORadj: 3.0 (CI95%: 1.5 - 5.5) and being vaccinated against seasonal influenza, ORadj: 7.1 (CI95%: 5.1 - 10.0). Being an individual with higher risk for influenza was not a determinant for pandemic influenza vaccine uptake. These determinants are not the same as those for seasonal influenza vaccination. Conclusions Overall A(H1N1)2009 influenza vaccine uptake remained low, particularly among individuals with higher risk for influenza and was lower than that observed for seasonal influenza. The reasons behind people's reluctance to be vaccinated need to be investigated further.